Evidence of Early Medieval Grain Exports from Barcelona to Al-Andalus - Thomas Freudenhammer (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2025)
The unexpected loss of a large cargo of barley taken on loan in Barcelona in 1021 suggests that the merchandise was intended for export. The Jewish merchant concerned, named Benevenisti, may have lost the cargo as a result of a shipwreck. An Arab source from the 11th century reports a maritime connection between the Muslim city of Tortosa, Barcelona and Narbonne, which was used by Jewish traders. Wrecks of Andalusian merchant ships off the Provençal coast show that this connection already existed at the turn of the 10th century. Jewish traders also appear to have travelled on these ships. The contacts between the Jewish communities of the coastal towns in question may have been used for trade transactions. The merchant Benevenisti could have exported his barley to Tortosa via this trade route
Keywords: N54; N74; N94; 330; 9th to 11th centuries; Barcelona; Al-Andalus; Tortosa; Al-Bakrī; Jewish merchants; grain trade